2022
DOI: 10.1002/adem.202101202
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Reconfiguring and Stiffening Origami Tube

Abstract: Reconfigurable structures have attracted increasing attention in numerous fields, such as aerospace, biomechanical, and civil engineering, owing to their nature to reshape and readjust without altering their original architectures. However, one of the most challenging issues in designing a reconfigurable structure is to ensure a load‐bearing capacity after reconfiguration, while keeping the structural flexibility during the transformation process. Here, an origami tube that can be easily reconfigured into mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…A single reconfigurable module is a thin-walled tubular structure based on the Yoshimura pattern, which is composed of isosceles triangles arranged to form a diamond pattern (Yoshimura, 1951). A recent study reported that this Yoshimurapatterned tube can be reconfigured to other geometrically feasible configurations, which reduces axial stiffness (Suh et al, 2022). The isolator proposed in this study consists of the reported Yoshimura-patterned tube, aimed to achieve both high static stiffness and suppression performance at the high-frequency by shifting the configuration on demands.…”
Section: Reconfigurable Module With Yoshimura Patternmentioning
confidence: 99%
See 2 more Smart Citations
“…A single reconfigurable module is a thin-walled tubular structure based on the Yoshimura pattern, which is composed of isosceles triangles arranged to form a diamond pattern (Yoshimura, 1951). A recent study reported that this Yoshimurapatterned tube can be reconfigured to other geometrically feasible configurations, which reduces axial stiffness (Suh et al, 2022). The isolator proposed in this study consists of the reported Yoshimura-patterned tube, aimed to achieve both high static stiffness and suppression performance at the high-frequency by shifting the configuration on demands.…”
Section: Reconfigurable Module With Yoshimura Patternmentioning
confidence: 99%
“…In the simplified dynamic model, k i and c i represent the axial stiffness and damping of i th reconfigurable module, respectively. Note that, the origami-based reconfigurable module composing the isolator has nonlinear static behavior under the axial loading condition (Suh et al, 2022); considering that the amplitude caused by the vibration is relatively small, however, the reconfigurable module is assumed to have a constant axial stiffness. The mass of the interlayer in between i 2 1 and i th modules is presented as m i in this model.…”
Section: Establishing Simplified Mathematical Model Of the Isolator S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, origami is a folding technique that involves assigning crease patterns to sheets. The origami-inspired foldable structure has been adopted in numerous deployable structures, due to the advantages of constructing various geometrical designs [5][6][7][8][9] and easily changing mechanical properties, such as stiffness [10,11]. Several studies [12,13] have explored applying origami structure concepts to deployable reflector antennas.…”
Section: Introductionmentioning
confidence: 99%
“…Origami enables the transformation of a structure's shape, size, and mechanical properties by folding thin flat sheets according to systematic patterns. Utilizing these unique properties, origami is increasingly applied not only in materials, robotics, biology, and architecture but also in aerospace engineering [1][2][3][4][5][6][7][8][9]. Moreover, origami techniques can be applied to not just micro-scale structures but also to large-scale structures exceeding meters in size like space architecture [10,11].…”
Section: Introductionmentioning
confidence: 99%